Proposed Business Strategy for PT Demarko Technology Innovation to Grab The Oppportunity of Asphalt Market in Indonesia - Mangihut, Martin; Toha, Mohammad (The Indonesian Journal of Business Administration, 2014)
Abstract. PT Demarko Technology Innovation is a subsidiary of PT Demarko Sinar Kemenangan. It was founded in purpose of research, development, and invention in applied technology and industry. Nowdays, the company has develop and maximize its invention in industry field including production of penetration 60/70 asphalt. Based on asphalt supply-demand data, national asphalt demand has not been meet with the availability of asphalt, that there is quite huge gap between supply and demand. Based on company’s data, in recent years, company has a stagnate production capacity and revenues. In this condition, company has to be able to grab the opportunity of huge asphalt market in Indonesia. This study will try to analyse what strategy that suite for the company to face this condition.To formulate business strategy, this study will use some of management tools. This study will analyse internal and external factor of the company, current strategy and its weaknesses, try to find root cause to solve the problem, and formulate business strategy with business model canvas, TOWS matrix and diamond strategy. From TOWS matrix, it shows that PT Demarko Technology Innovation is located in Quadrant I in Strength-Opportunities(S-O) area, so the company potentially to growth. With TOWS matrix, business model canvas and diamond strategy, PT Demarko Technology Innovation expected to be able to supply more asphalt for Indonesian asphalt demand, company need to applied an aggressive strategies through increase promotion and partnerships,buy new production machine and also expand its marketing area. With diamond strategy, company’s strategies will be based on arena that company will faced, differentiators from competitors, vehicle to achieve, staging to achieve, and economic logic the proposed strategies. To implement the proposed strategies, the company need to implement it through each of functional division, consist of marketing strategy, financial strategy, research and development strategy, operational strategy, human resource strategy, and information technoogy strategy, and also human resource allocation. This study will provide time schedule to implement the proposed strategy.Key words : asphalt, penetration asphalt, business strategy, diamond strategy, demarko technology innovation, demarko, bentonas